How Parental Co-Viewing Can Reduce the Adverse Effects of Gadgets in Early Children (PIAUD IAIN Kudus, 2022)
This research is motivated by parents' concerns about the dangers posed by gadgets, parental co-viewing has been suggested as a way to prevent negative harm from gadgets. The purpose of this study was to determine parental co-viewing and involvement in the use of gadgets in reducing the dangers caused by gadgets. This study uses a qualitative method with a case study research design on three parents who have children aged 2-5 years. The data collection technique uses interviews and field notes which are then processed using grounded theory analysis techniques. The results of this study indicate that parents use parental co-viewing because through this parental mediation parents will know and supervise children's digital activities so that they can reduce the dangers of gadgets. In addition, this parental co-viewing also increases the closeness of parents with their children. Activities carried out by parents with their children are watching educational videos on the YouTube application and playing game on educational game applications. Parental Co-viewing can be a guide for parents to help early childhood to avoid the dangers posed by the device because parents can organize and know the content that will be accessed by their children.